3-D modelling and statistical properties of surface pits of corroded wire based on image processing technique. (October 2016) - Xu, Yang; Li, Hui; Li, Shunlong; Guan, Xinchun; Lan, Chengming
Highlights: Conducted 3D surface pit depth measurement of corroded high-strength steel wires. Visualized and characterized corroded surface based on image processing method. Analyzed geometric and morphology parameters of corrosion pits statistically. Observed two geometrical modes and five maximum depth categories of pits. Abstract: A method based on image processing was proposed in this study to visualize and model surface pits of high-strength steel wire. Surface measurement based on infinite focus was employed to measure the pit depth all over the cylindrical surface. Corrosion pits were visually identified by a binary image with a greyscale threshold clustered by the optimal entropy threshold method. Ellipse approximation was simulated to precisely characterize individual corrosion pits, and the geometric and morphological parameters of the corrosion pits were calculated and statistically analysed. The proposed method provides an effective approach for 3D corrosion pit modelling.